Bolivia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Authorities of Bolivia. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that Bolivia's real GDP is expected to grow by 4 percent in 2017, relatively strong by regional standards. Accommodative fiscal policy, strong credit growth, and robust private consumption are expected to continue supporting activity while the fiscal and external current account deficits are likely to persist in the medium term. With weak private investment and the end of the commodity boom, growth is forecast to moderate gradually to 3.7 percent in the medium term. Key risks to this outlook include failure to discover new natural gas fields, further dollar strength, or lower-than-expected gas and minerals prices.